Indian practical civil engineers’ handbook - Khanna, Prem Nath (Engineers’ Publishers & Advertisers, 1997)
The object this volume is to give a fairly complete but concise account of the various subjects to serve as a ready reference for everyday-work problems which constantly co-front the engineers,...